IMPORTANT TASKS FOR RAISING THE MORALE OF YOUNG PEOPLE AND MEANINGFUL ORGANIZATION OF THEIR FREE TIME WERE DETERMINED - Abdullayev Nodirbek No’monovich (Academia Science Repository, 2023)
30% of the population of our country are young people between 14 and 30 years old. Modern conditions and opportunities have been created for their education and occupation. At the same time, organization of meaningful free time of young people is an urgent issue. The more spiritually perfect young people are, the stronger their immunity against various foreign diseases will be. It is known that the head of our state put forward 5 important initiatives to start work in the social, spiritual and educational spheres on the basis of a new system. The first initiative serves to increase the interest of young people in music, painting, literature, theater and other types of art, and to reveal their talent. The second initiative is aimed at physical training of young people and creation of necessary conditions for them to show their abilities in the field of sports. The third initiative is aimed at organizing the effective use of computer technologies and the Internet among the population and young people. The fourth initiative is aimed at organizing systematic work on raising the spirituality of young people and widely promoting reading among them. The fifth initiative provides for women’s employment issues.